COMPLEX TREATMENT OF HELICOBACTER PYLORI INFECTION WITH RIFAXIMIN IN CHILDREN - A.A. Nizhevich (Voprosy Sovremennoj Pediatrii, 2009)
Authors studied an effectiveness of antibiotic rifaximin in complex treatment of Helicobacter pylori infection in children. They observed 41 children in the age 12–17 years old (23 girls and 18 boys). The diagnosis of pyloric helicobacteriosis proved by histology and bacterioscopy with Gimze stain combined with urease test. All children were treated according to the study program with the use of medications: bismuth (De-Nol) — 1 tablet 3 times daily (14 days) + rabeprasole (Pariet) 1 mg/kg once daily (14 days) + rifaximin (Alfa Normix) 400 mg twice daily (10 days) + amoxicillin 50 mg/kg twice daily (10 days). The control of eradication of H. pylori was performed after 4–6 weeks after the end of a treatment with a respiratory test. Eradication was achieved in 36 (87,8%) of children. All patients were adherent to the treatment, and there were no severe adverse reactions during the study.Key words: children, Helicobacter pylori, ulcer, rifaximin, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(6):106-108)